2003
DOI: 10.2975/27.2003.10.17
|View full text |Cite
|
Sign up to set email alerts
|

Development of the competency assessment tool-mental health, an instrument to assess core competencies for mental health care workers.

Abstract: As the focus on accountability in health care increases, there has been a corresponding emphasis on establishing core competencies for health care workers. This article discusses the development of an instrument to establish core competencies for workers in inpatient mental health settings. Twenty-six competencies were identified and rated by mental health care personnel on two subscales: the importance of the competency and how much behavioral health care workers could benefit from training on the competency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 8 publications
1
22
1
Order By: Relevance
“…Our results also overlap with some of the core competencies identified in the general literature on behavioral health competencies. Many of the studies cited in the introduction emphasize the importance of outreach, empathy, professionalism and teamwork in the successful delivery of behavioural health services (Coursey et al 2000a, b;Clasen et al 2003;Young et al 2000;Aubry et al 2005). Characteristics and competencies which may be more unique to supported employment specialists include initiative, hardiness, persistence and professionalism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results also overlap with some of the core competencies identified in the general literature on behavioral health competencies. Many of the studies cited in the introduction emphasize the importance of outreach, empathy, professionalism and teamwork in the successful delivery of behavioural health services (Coursey et al 2000a, b;Clasen et al 2003;Young et al 2000;Aubry et al 2005). Characteristics and competencies which may be more unique to supported employment specialists include initiative, hardiness, persistence and professionalism.…”
Section: Discussionmentioning
confidence: 96%
“…This details specific competencies, behaviors and attitudes of behavioral health workers that may influence performance in the field. These commonly consist of checklists of desirable competencies ranging in size from 12 (Courseyet al 2000a, b) to 26 (Clasen et al 2003) to 37 (Young et al 2000) to 59 (Aubry et al 2005). These lists generally consist of broad competencies such as respect, optimism and outreach; and specific competencies such as paying attention to client preferences, coordination of medical care and knowledge of entitlements.…”
Section: Introductionmentioning
confidence: 99%
“…While prior research (Clasen et al, 2003) has found a reliable overall measure of competency assessment for mental health professionals, to the authors' knowledge, this is the first study to develop reliable performance domain scales specific to PRPs for both frequency and importance ratings. As such, this study expanded prior nonpublished work finding a seven-performance domain, 75-item PRP task scale (Henderson & Bugbee, 2000) for the International Association for Psychosocial Rehabilitation Services.…”
Section: Discussionmentioning
confidence: 97%
“…The specific strength of this study is that it has many advantages: it enables to investigate the stepwise implementation of new ideas over time, in a practical situation that does not permit to deliver the intervention simultaneously to all participants [20]. Because of the stepwise implementation of the new recovery concept, professionals could maintain their routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to implement a more recovery-oriented care system, it is important to focus on the professional's belief in and understanding of recovery, and the ability to promote patient recovery [10, 11]. Moreover, professionals who have to assimilate a new recovery vision into their routine practice need to master a set of core competencies [20]. These competencies include effective communication, fostering hope, appropriate self-disclosure, and a mutual respectful partnership in treatment.…”
Section: Introductionmentioning
confidence: 99%